(untitled) (INNOVATIVE ECONOMY, 2026)
Andrusyk V.V. INSTITUTIONAL TRANSFORMATION OF COMPETITIVE INTERACTION IN THE GLOBAL SEMICONDUCTOR MARKET: FROM MARKET-BASED TO STATE-STRATEGIC INDUSTRY ORGANIZATION REGIME Purpose. The aim of this article is to investigate the patterns of institutional transformation of competitive interactions in the global semiconductor market, particularly the transition from a predominantly market-based to a state-strategic mode of industry organization. Methodology. A set of general scientific and specialized research methods was used in the study. The method of comparative analysis was applied in examining government support programs for the semiconductor industry across six leading world economies (the United States, the European Union, China, South Korea, Japan, and India) with regard to funding volumes, policy instruments, and strategic objectives. The method of systematization was used to classify state-strategic regulatory instruments into stimulative, restrictive and coordinative categories. The method of generalization was employed to formulate the patterns governing the transition from a market-based to a state-strategic mode of industry organization and its consequences for the competitive structure of the market. The method of statistical analysis was applied to examine the dynamics of the global semiconductor market and its structural changes. The study draws upon data from the Semiconductor Industry Association, analytical reports by KPMG and the Centre for Strategic and International Studies, materials from the European Court of Auditors, as well as official documents issued by government bodies of leading economies. Findings. It has been established that the global semiconductor market is undergoing systemic institutional transformation driven by the pandemic-induced supply chain crisis, the intensification of technological rivalry, and the emergent recognition of the critical role of semiconductors in national security. A study of industry support programs across six leading economies, each with a combined gross domestic product exceeding one trillion dollars, has been conducted. A convergence of strategic approaches has been identified alongside a simultaneous differentiation of the instruments employed, determined by initial competitive positions. The contradictory impact of transformation on the global value chain is explored, manifested in the paradox of the positive impact of geographic diversification of production combined with the risk of technological bifurcation and diminished efficiency. Originality. The theoretical substantiation of the institutional transformation of the global semiconductor market as a transition from a market-based to a state-strategic mode of industry organization has been further developed, which, unlike existing studies that focus on the analysis of individual national programs, enables this process to be examined as a systemic pattern inherent to all leading economies regardless of their political system. The classification of state-strategic regulatory instruments for the semiconductor industry has been refined through their division into stimulative, restrictive, and coordinative categories, which enables a more comprehensive assessment of the impact of institutional changes on the competitive structure of the market. Practical value. The findings of this study may be utilized in the formulation of state policy for the development of high-technology industries, particularly in substantiating strategies for integration into global semiconductor value chains for countries seeking to enter this sector. The comparative analysis of government support programs may serve as an analytical foundation for the development of corresponding national initiatives. Key words: semiconductor market, institutional transformation, state-strategic regime, competitive interaction, industrial policy, value chains, technological sovereignty.